2020
DOI: 10.1111/jpc.14903
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and paediatric health services: A survey of paediatric physicians in Australia and New Zealand

Abstract: Aims: COVID-19 is now a global pandemic. At the time of survey, fewer than 150 children in Australia and New Zealand had documented infection. The aim of this study was to assess attitudes, readiness and confidence in the early stages of the COVID-19 pandemic through an online survey of paediatric physicians and sub-specialists across Australia and New Zealand. Methods: Multiple email list groups were used to contact paediatric physicians to undertake an online Likert scale survey between 17 and 24 March. Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Our database keyword search identified a further 218 relevant studies. Of a total of 1089 identified studies, 59 met our inclusion criteria for this systematic review ( Huang et al., 2020 ; Abdessater et al., 2020a , b ; Ahmed et al., 2020 ; Behnam et al., 2020 ; Bohlken et al., 2020 ; Cai et al., 2020 ; Cai et al., 2019 ; Cao et al., 2020 ; Chen et al., 2020a , b ; Chew et al., 2020 ; Chung and Yeung, 2020 ; Davico et al., 2020 ; Foley et al., 2020 ; Gautam et al., 2020 ; Guo et al., 2020 ; Hong et al., 2020 ; Hu et al., 2020 ; Jiang et al., 2020 ; Kang et al., 2020 ; Ko et al., 2020 ; Lai et al., 2019 ; Li et al., 2020a , b ; Liang et al., 2020 ; Liu et al., 2020a , b , c , d ; Louie et al., 2020 ; Lu et al., 2020 ; Lv et al., 2020 ; Martin, 2020 ; Mo et al., 2020 ; Mohindra et al., 2020 ; Naser, 2020 ; Nemati et al., 2020 ; Ni et al., 2020 ; Pu et al., 2020 ; Rajkumar et al., 2020 ; Schulte et al., 2020 ; Shen et al., 2020a , b ; Simpson et al., 2020 ; Sun et al., 2020 ; Tan et al., 2020 ; Wu et al., 2020a , b ; H Xiao et al., 2020 , 70 ; Yifan et al., 2020 ; Yin and Zeng, 2020 ; Yuan et al., 2020 ; ...…”
Section: Resultsmentioning
confidence: 99%
“…Our database keyword search identified a further 218 relevant studies. Of a total of 1089 identified studies, 59 met our inclusion criteria for this systematic review ( Huang et al., 2020 ; Abdessater et al., 2020a , b ; Ahmed et al., 2020 ; Behnam et al., 2020 ; Bohlken et al., 2020 ; Cai et al., 2020 ; Cai et al., 2019 ; Cao et al., 2020 ; Chen et al., 2020a , b ; Chew et al., 2020 ; Chung and Yeung, 2020 ; Davico et al., 2020 ; Foley et al., 2020 ; Gautam et al., 2020 ; Guo et al., 2020 ; Hong et al., 2020 ; Hu et al., 2020 ; Jiang et al., 2020 ; Kang et al., 2020 ; Ko et al., 2020 ; Lai et al., 2019 ; Li et al., 2020a , b ; Liang et al., 2020 ; Liu et al., 2020a , b , c , d ; Louie et al., 2020 ; Lu et al., 2020 ; Lv et al., 2020 ; Martin, 2020 ; Mo et al., 2020 ; Mohindra et al., 2020 ; Naser, 2020 ; Nemati et al., 2020 ; Ni et al., 2020 ; Pu et al., 2020 ; Rajkumar et al., 2020 ; Schulte et al., 2020 ; Shen et al., 2020a , b ; Simpson et al., 2020 ; Sun et al., 2020 ; Tan et al., 2020 ; Wu et al., 2020a , b ; H Xiao et al., 2020 , 70 ; Yifan et al., 2020 ; Yin and Zeng, 2020 ; Yuan et al., 2020 ; ...…”
Section: Resultsmentioning
confidence: 99%
“…57 HCWs availability and willingness to work is therefore directly related to capacity within the healthcare system. 36,58 Surge planning will need to incorporate contingencies for HCW availability and adjust resources and maximum capacity ratings accordingly. 59 Clearly, there is a need for open honest communications from management, and timely information on matters such as PPE supplies.…”
Section: With Regard To Social Distancing From Family Social Distancing From Community Members Ormentioning
confidence: 99%
“…Psychological distress and anxiety can be caused by: the fear of being infected and contaminating their families [8], [14], [29], [48], [58], [60], [64], [76]- [78]; the lack of knowledge and unavailability of clear protocols [28], [45], [58]; shortages of medical supplies and effective PPE [13], [14], [33], [40], [45], [52], [58], [63]; heavy workloads [13], [14], [28], [59], [60], [68], [78]; the disruption of training programs [14]; quarantine measures and isolation [56]; the overwhelming quantity of information in the media, including social media [62], [77]; concerns about their financial situation, mostly for surgeons because of the reduction of surgical and clinical activities [56]. Some studies reported measures considered to be effective in reducing HCWs' anxiety: institutional support and recognition of their work by the medical profession and hospital management [58]; family or social support [13], [40], [58], [59], [62]; better virus prevention and transmission knowledge [58]; implementation of clear disease prevention guidelines [58]; a positive working environment ...…”
Section: Effects Of the Pandemic On Hospitals' Professionalsmentioning
confidence: 99%